The Cup of Gaius Valerius Verdullus found at Arcobriga (Monreal de Ariza, Zaragoza) - Baratta, Giulia (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
In this paper I present two fragments from a fine walled ceramic vase found in Arcobriga that are part of the production of Gaius Valerius Verdullus, and I advance some views regarding the restoration of the epigraphic text that characterizes it.